1998
DOI: 10.3109/01913129809032262
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Spindle Cell Carcinoma of the Kidney

Abstract: The authors report a renal cell carcinoma composed largely of spindle cells of Fuhrman's nuclear grade II in which the bland appearance of the cells and low mitotic index were reminiscent of a benign or low-grade smooth muscle tumor. Keratin immunostaining was positive, but evidence of epithelial differentiation was obtained by electron microscopy. The tumor was an incidental finding and it did not invade the perirenal fat or the renal vein. Follow-up is only 24 months but the histological features suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
1
22
1
2
Order By: Relevance
“…1,2 Until its recognition as a distinct neoplastic entity by the World Health Organization (WHO) consensus conference, mucinous tubular and spindle cell carcinoma had been previously sporadically reported with a variety of names, usually pointing out the morphologic relationships with the distal nephron and the loop of Henle or highlighting the spindle cell component. [3][4][5][6][7][8][9][10][11] Since mucinous tubular and spindle cell carcinomas have generally been described as low-grade and low-stage malignancies, usually cured by surgery, 1,4,8,[12][13][14] differentiation from other primary malignancies of the kidney is important. The differential diagnosis has to take into consideration primarily papillary renal cell carcinoma, type 1, that may share with mucinous tubular and spindle cell carcinomas several pathologic features, such as tubular, trabecular or papillary architecture, lowgrade or moderate nuclear atypia, and the presence of foamy macrophages and inflammatory cells.…”
mentioning
confidence: 99%
“…1,2 Until its recognition as a distinct neoplastic entity by the World Health Organization (WHO) consensus conference, mucinous tubular and spindle cell carcinoma had been previously sporadically reported with a variety of names, usually pointing out the morphologic relationships with the distal nephron and the loop of Henle or highlighting the spindle cell component. [3][4][5][6][7][8][9][10][11] Since mucinous tubular and spindle cell carcinomas have generally been described as low-grade and low-stage malignancies, usually cured by surgery, 1,4,8,[12][13][14] differentiation from other primary malignancies of the kidney is important. The differential diagnosis has to take into consideration primarily papillary renal cell carcinoma, type 1, that may share with mucinous tubular and spindle cell carcinomas several pathologic features, such as tubular, trabecular or papillary architecture, lowgrade or moderate nuclear atypia, and the presence of foamy macrophages and inflammatory cells.…”
mentioning
confidence: 99%
“…The features most commonly encountered -cytokeratin demonstrated by immunohistochemistry, and tonofilaments and desmosomes by electron microscopy [3,17,25,26,30,32,34,35,39,44,47,50,56,57,61,64,66] -permit distinction from a non-epithelial spindle-cell malignancy. In addition to showing epithelial features, however, some spindle-cell carcinomas show organelles that are more typical of mesenchymal cells, and the term spindle-cell carcinoma with "mesenchymal metaplasia" has been used [16].…”
Section: Discussionmentioning
confidence: 98%
“…Spindle-cell carcinoma is a variant of carcinoma in which epithelial features such as desmosomes and tonofibrils [3,17,25,26,30,32,34,35,39,44,47,50,57,59,61,64,66] may be co-expressed with organelles more usually associated with mesenchymal cells, i.e., abundant rough endoplasmic reticulum (rER) [1,11,14,18,21,22,28,31,36,37,38,43,45,55,56,62,63,64,65] and the myofilaments with focal densities typical of smooth-muscle cells [1,2,14,16,19,24,28,37,40]. rER and myofilaments, in addition to being found separately in fibroblasts and smooth-muscle cells, are colocalised in the myofibroblast.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the tumors were predominantly hypodiploid (DNA-indexes 0.77 and 0.80), whereas the third tumor was hypertriploid (1.57) as measured by DNA-image cytometry. From the latter tumor live cells were available making it possible to establish its karyotype: 62-70,XXX,Interphase fluorescence in situ hybridization analyses with centromere-specific probes for chromosomes 1,3,4,6,7,9,10,17,18,20, and X showed that the two hypodiploid tumors had disomic and monosomic chromosome populations, whereas the karyotyped, near-triploid tumor was dominated by trisomic chromosome populations. Comparative genomic hybridization analysis was normal for the karyotyped tumor but abnormal for the two others.…”
mentioning
confidence: 99%
“…In the late 1990s, several reports describing low-grade, unclassified renal cell carcinomas (RCC) exhibiting mucinous, tubular, and spindle cell features and minimal mitotic activity were published, [1][2][3][4] culminating in the WHO acceptance of these tumors as a distinct and new subgroup of RCC. 5 A recent publication reviews clinical, pathological, and genomic characteristics of this new tumor entity.…”
mentioning
confidence: 99%